2023
DOI: 10.1002/advs.202207571
|View full text |Cite
|
Sign up to set email alerts
|

Halide Double Perovskite Nanocrystals Doped with Rare‐Earth Ions for Multifunctional Applications

Abstract: Most lead-free halide double perovskite materials display low photoluminescence quantum yield (PLQY) due to the indirect bandgap or forbidden transition. Doping is an effective strategy to tailor the optical properties of materials. Herein, efficient blue-emitting Sb 3+ -doped Cs 2 NaInCl 6 nanocrystals (NCs) are selected as host, rare-earth (RE) ions (Sm 3+ , Eu 3+ , Tb 3+ , and Dy 3+ ) are incorporated into the host, and excellent PLQY of 80.1% is obtained. Femtosecond transient absorption measurement found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…This distinct behavior leads to the exploration of CsCaCl 3 :Mn 2+ nanocrystals for optical thermometry. To this end, the fluorescence intensity ratio (FIR) technique is employed to establish a correlation between temperature and FIR, as elucidated by the equations: 34,35 …”
Section: Resultsmentioning
confidence: 99%
“…This distinct behavior leads to the exploration of CsCaCl 3 :Mn 2+ nanocrystals for optical thermometry. To this end, the fluorescence intensity ratio (FIR) technique is employed to establish a correlation between temperature and FIR, as elucidated by the equations: 34,35 …”
Section: Resultsmentioning
confidence: 99%
“…For SWIR PL of Yb/ Er/Bi-codoped Cs 2 NaInCl 6 NCs, under ultraviolet irradiation, the S → P transition of Bi 3+ in the [BiCl 6 ] 3− octahedron is activated, which causes the carriers to be in the excited state, implying that there should be an energy-transfer process from the [BiCl 6 ] 3− -induced trap state to the [ErCl 6 ] 3− octahedron. This is a typical photophysical process in inorganic halide DPs containing both ns 2 electron dopants and lanthanides that has been reported, 12,13,22,24,41,42 and it is reasonable to deduce that the [BiCl 6 ] 3− -induced trap state is an STE state.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
“…Recently, all-inorganic lead-free indium-based halide double perovskite (DP) Cs 2 MInCl 6 (M = Na or Ag) NCs have aroused scientific interest because of their three-dimensional structure, direct band gap, and unique optical and photoelectronic characteristics. Unfortunately, the parity-forbidden transition of Cs 2 MInCl 6 NCs severely hinders their photon absorption processes, which is a critical issue for the very low luminescence efficiency of pristine DP NCs. , Remarkably, Tang’s group and Han’s group respectively doped Bi 3+ and codoped Bi 3+ /Na + ions into Cs 2 AgInCl 6 , which broke the parity-forbidden transition and passivated the defect trap state, thereby realizing the warm-white-light emission caused by self-trapped excitons (STEs). Obviously, the doping/codoping strategy is an effective way to tailor and optimize the luminescence properties of Cs 2 MInCl 6 NCs. Subsequently, Saikia et al showed that Cs 2 NaInCl 6 has better UV radiation stability than Cs 2 AgInCl 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping halide double perovskites (HDPs) of the general formula Cs 2 B′ 1+ B″ 3+ X 6 (B′ 1+ = Na + , Ag + ; B″ 3+ = Bi 3+ , Sb 3+ , In 3+ ; and X = Cl – , Br 1– , I – ) with metal ions has recently emerged as a new avenue to tailor the physical properties of lead-free and solution-processed semiconducting perovskites, highlighting potential applications in optoelectronics and spintronics. Incorporating transition-metal ions such as Fe 3+ , Cr 3+ , and V 3+ into a B″-site of an HDP host has led to many interesting properties, such as bandgap tuning, , efficient near-infrared light emissions, , and magnetic response . Nonetheless, many puzzles remain regarding the role of transition-metal doping/alloying of HDPs, apart from target applications expected from ideal metal-ion substitutions at the B′-site or B″-site (i.e., with the correct charge states and correct crystallographic positions).…”
mentioning
confidence: 99%